Hyperosmolarity Impairs Human Extravillous Trophoblast Differentiation by Caveolae Internalization - Reppetti, Julieta; Medina, Yollyseth; Farina, Mariana; Damiano, Alicia E.; Martínez, Nora Alicia (Frontiers in Physiology, 2021)
We recently reported that an intact caveolar structure is necessary for adequate cell migration and tubulogenesis of the human extravillous trophoblast (EVT) cells. Emerging evidence supports, that hyperosmolarity induces the internalization of caveolae into the cytoplasm and accelerates their turnover. Furthermore, signaling pathways associated with the regulation of trophoblast differentiation are localized in caveolae. We hypothesized that hyperosmolarity impairs EVT differentiation and caveolae/Cav-1 participates in this process. EVT cells (Swan 71 cell line) were cultured in complete Dulbecco's modified Eagle medium/Nutrient Mixture F-12 and exposed to hyperosmolar condition (generated by the addition of 100 mM sucrose). Hyperosmolarity altered the EVT cell migration and the formation of tube-like structures. In addition, cell invasion was decreased along with a reduction in the latent and active forms of MMP‐2 secreted by these cells. Regarding Cav-1 protein abundance, we found that hyperosmolarity enhanced its degradation by the lysosomal pathway. Accordingly, in the hyperosmolar condition, we also observed a significant increase in the number of vacuoles and the internalization of the caveolae into the cytoplasm. Taken together, our findings suggest that hyperosmolarity may induce caveolae internalization and increase their turnover, compromising the normal differentiation of EVT cells.